Crop Damage by Granivorous Birds Despite Protection Efforts by Human Bird Scarers in a Sorghum Field in Western Kenya - Hiron, Matthew; Rubene, Diana; Mweresa, Collins K.; Ajamma, Yvonne U.O.; Owino, Eunice A.; Low, Matthew (Journal of African Ornithology, 2014)
Cereal crop damage from granivorous birds poses a serious food security problem for subsistence farmers in sub-Saharan Africa. In this region, farmers may rely on human ‘bird scarers’ to limit crop damage. Here we report feeding behaviour and crop damage patterns caused by Village Weavers Ploceus cucullatus and African Mourning Doves Streptopelia decipiens during four days in a 0.12 ha sorghum field protected by two full-time bird scarers in western Kenya. Despite the scarers’ efforts, almost 60% of the seed was lost before harvest. Bird abundance was largely determined by the presence of the bird scarers, with seed loss patterns being a function of distance from these people. Throughout the day, an average of 18 weavers (maximum 120) was present on the crop in any five-minute period. The number of mud projectiles thrown at the birds per 15 min showed only minor diurnal fluctuations, further suggesting that seed eaters attacked the crop throughout the day. Village Weaver individuals took an average 16 seeds per visit, whereas dove individuals took 32 seeds (maximum 105 and 455, respectively). Our study illustrates that avian crop pests can be extremely persistent and, even with consistent diurnal bird scaring activity, severely damage a small crop field. Bird scarers need to be active throughout daylight hours and patrol both the centres and edges of fields to create maximum disturbance to foraging seed eating birds. Further research is needed in order to investigate effects of local- and landscape-level land use patterns on the feeding behaviour of crop pests and the effectiveness of crop protection measures.